2009
DOI: 10.1002/pros.21048
|View full text |Cite
|
Sign up to set email alerts
|

No association between variant DNA repair genes and prostate cancer risk among men of African descent

Abstract: Recent reports hypothesize that multiple variant DNA repair gene interactions influence cancer susceptibility. However, studies identifying high-risk cancer-related genes use single gene approaches that lack the statistical rigor to model higher-order interactions. To address this issue, we systematically evaluated individual and joint modifying effects of commonly studied polymorphic base and nucleotide excision repair genes relative to prostate cancer (PCA) risk using conventional logistic regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…The associations between APE1 T1349G polymorphism and risk of other types of cancers have not been fully assessed in currently available studies [21][22][23][24]. In addition, studies on the association between APE1 T1349G polymorphism and risk of prostate cancer remained inconclusive [7,10,[13][14][15][16]. Therefore, we performed this present meta-analysis to precisely assess the association between APE1 T1349G polymorphism and prostate cancer risk.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The associations between APE1 T1349G polymorphism and risk of other types of cancers have not been fully assessed in currently available studies [21][22][23][24]. In addition, studies on the association between APE1 T1349G polymorphism and risk of prostate cancer remained inconclusive [7,10,[13][14][15][16]. Therefore, we performed this present meta-analysis to precisely assess the association between APE1 T1349G polymorphism and prostate cancer risk.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, those seven studies contained a total of 3,063 individuals [7,10,[13][14][15][16]. Among those seven studies, three studies were from Asian population, two were from Caucasians, and the other two were from Africans [7,10,[13][14][15][16]. The main characteristics of seven studies included into the meta-analysis were shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations